The labour market position of second-generation immigrants in Belgium - Vincent Corluy; Joost Haemels; Ive Marx; Gerlinde Verbist (National Bank of Belgium, 2015)
Belgium has one of the largest gaps in labour market outcomes between natives and individuals of foreign origin. One might expect that the children of migrants (the so-called second generation) would perform better than the first generation, as they ought to have a better knowledge of the local language, better educational qualifications and greater opportunities for work experience in the domestic labour market. On the basis of data from the ad hoc module of 2008 Labour Force Survey (LFS) we find that employment rates for generation migrants in Belgium are hardly better than those for first generation migrants. This finding stands in marked contrast what is found in neighbouring countries. Using a unique combination of data sources, we examine the labour market position of second-generation migrants in more depth. We find considerable variation in labour market outcomes by country of origin and a Fairlie decomposition yields that education is an important explanatory factor of the employment rate gap. Yet there still remains a large unexplained part.
Keywords: J15; J21; J24; J61; 330; Second generation immigrants; labour market outcomes; decomposition methods; educational attainment; Einwanderung; Arbeitsmarktintegration; Junge Arbeitskräfte; Jugendarbeitslosigkeit; Bildungsniveau; Vergleich; Dekompositionsverfahren; Belgien